Evaluation of Local Skeletal Muscle Blood Flow in Manipulative Therapy by Diffuse Correlation Spectroscopy - Matsuda, Yasuhiro; Nakabayashi, Mikie; Suzuki, Tatsuya; Zhang, Sinan; Ichinose, Masashi; Ono, Yumie (Frontiers in Bioengineering and Biotechnology, 2022)
Manipulative therapy (MT) is applied to motor organs through a therapist’s hands. Although MT has been utilized in various medical treatments based on its potential role for increasing the blood flow to the local muscle, a quantitative validation of local muscle blood flow in MT remains challenging due to the lack of appropriate bedside evaluation techniques. Therefore, we investigated changes in the local blood flow to the muscle undergoing MT by employing diffuse correlation spectroscopy, a portable and emerging optical measurement technology that non-invasively measures blood flow in deep tissues. This study investigated the changes in blood flow, heart rate, blood pressure, and autonomic nervous activity in the trapezius muscle through MT application in 30 volunteers without neck and shoulder injury. Five minutes of MT significantly increased the median local blood flow relative to that of the pre-MT period (p < 0.05). The post-MT local blood flow increase was significantly higher in the MT condition than in the control condition, where participants remained still without receiving MT for the same time (p < 0.05). However, MT did not affect the heart rate, blood pressure, or cardiac autonomic nervous activity. The post-MT increase in muscle blood flow was significantly higher in the participants with muscle stiffness in the neck and shoulder regions than in those without (p < 0.05). These results suggest that MT could increase the local blood flow to the target skeletal muscle, with minimal effects on systemic circulatory function.